Association of Anti Phospholipid Antibodies in The Patients With Ischemic Stroke Under 45 Years of Age In Tertiary Level Hospital: A Case Control Study (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Antiphospholipid antibodies have been associated with a clinical syndrome consisting of thrombosis and recurrent, unexplained fetal loss. Stroke may be caused by Antiphospholipid Antibodies (APLA) especially in young persons without other conventional risk factors like Diabetes mellitus, Hypertension, Dyslipidemia, Smoking etc. The aim of this study was to evaluate the association of antiphospholipid antibodies (Anticardiolipin antibody and lupus anticoagulant) in young ischemic stroke patients presenting with sudden neurological deficit. Materials and methods: This was a case-control study performed in Medicine and Neurology department of Chittagong Medical College Hospital, Chittagong, a tertiary care government hospital. A total no. of 195 respondents consisting of 95 consecutive young patients (Age less than 45 years) diagnosed as ischemic stroke and 100 age and sex matched healthy controls were included in this study. The clinical details and related investigations of the respondents were reviewed. Anticardiolipin antibodies (IgM, IgG isotypes) were evaluated by an Enzyme-Linked Immunosorbent Assay (ELISA) and lupus anticoagulant by phospholipid dependent coagulation test Activated Partial Thromboplastin Time (APTT). When APTT was found more than 5 sec prolonged than control value, mixing studies using a 50:50 mixture of patient and normal plasma were performed and the result was considered positive if prolongation of APTT was not corrected which were needed to be confirmed after 12 weeks. The tests of Anticardiolipin antibodies (aCL) were repeated after 12 weeks when prior results were abnormal and the tests were considered positive when both results of aCL were found above normal value (IgM > 7.2 MPL/ml, IgG>14.4 GPL/ml). Results: Anticardiolipin antibodies Anticardiolipin antibodies (aCL) were present in 10.5% of the patients (IgM in 3 cases, IgG in 6 cases, IgM/IgG both in 1 case) and in 1% (IgG type) of control, but none of the study subjects were found LA positive. The odds ratio of aCL was 11.647 (95% Confidence interval= 1.461 – 92.852). Overall, the risk factors profile in cases were, Hypertension (32.6%) Diabetes mellitus (10.5%) Cigarette smoking (26.3%) and Dyslipidaemia (25.3%). Among the 10 aCL positive cases, 3 were Hypertensive, 1 was Diabetic, 2 were Smoker and 2 were Dyslipidemic but anticardiolipin antibody positive group did not differ significantly with respect to distribution of major risk factor frequency from anticardiolipin antibody negative group. Conclusion: Anticardiolipin antibodies are associated significantly with ischemic stroke in young patients less than 45 years of age (p= 0.004). Hence screening for anti-cardiolipin antibodies in young patients with stroke is recommended.JCMCTA 2017 ; 28 (2) : 27-33